Detecção de comunidades em grafos - Teixeira, Marcélia Picolotto da Silva (2018)
In this work we present the minimum cut method for the detection of communities in graphs, we illustrate the method with examples and we propose an work routine such that the math teacher could apply communities detection activity for high school students, where it is up to them to detect communities in graphs that represent networks of their daily lives. In the proposed method and activities the matrix subject is treated in a unusual way, not associated with the resolution of linear systems, applying eigenvalues and eigenvectors.